ChemInform Abstract: A Supermolecular Building Approach for the Design and Construction of Metal—Organic Frameworks. Issue 43 (21st October 2014) - Guillerm, Vincent; Kim, Dongwook; Eubank, Jarrod F.; Luebke, Ryan; Liu, Xinfang; Adil, Karim; Lah, Myoung Soo; Eddaoudi, Mohamed
Abstract Review: 243 refs.